2011
DOI: 10.1111/j.1365-2966.2011.18719.x
|View full text |Cite
|
Sign up to set email alerts
|

Stark width regularities within magnesium spectral series

Abstract: The dependences of electron‐ and proton‐impact Stark width on the upper‐level ionization potential within different series of neutral magnesium spectral lines have been evaluated and discussed. Dependences similar to those previously found for the electron‐impact contribution were also obtained for the proton‐impact contribution to the Stark broadening parameters. The emphasis is on the fine‐structure influence on the studied Stark parameter dependences. The relations found can be used in both cases for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Therefore, the aim of this paper is to study the dependences of electron, proton and ionized helium impact contributions to the Stark widths of helium neutral spectral lines originating from different spectral series on the upper‐level ionization potential. This is in continuation to already published papers devoted to regularities within the spectral series of Mg i (Tapalaga, Dojčinović & Purić 2011) and Be i (Dojčinović, Tapalaga & Purić 2011) spectral series. The emphasis will be on the term structure influence on the studied Stark parameter dependences.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, the aim of this paper is to study the dependences of electron, proton and ionized helium impact contributions to the Stark widths of helium neutral spectral lines originating from different spectral series on the upper‐level ionization potential. This is in continuation to already published papers devoted to regularities within the spectral series of Mg i (Tapalaga, Dojčinović & Purić 2011) and Be i (Dojčinović, Tapalaga & Purić 2011) spectral series. The emphasis will be on the term structure influence on the studied Stark parameter dependences.…”
Section: Introductionsupporting
confidence: 85%
“…These relations were successfully fitted to a number of spectral lines, as shown in a series of articles (see e.g. Purić et al 1993; Purić & Šćepanović 1999; Purić et al 2008; Tapalaga et al 2011), and were found to be of the form where w is the line width expressed in angular frequency units, if χ is the corresponding upper‐level ionization potential expressed in eV, and a and b are fitting coefficients for chosen temperature and electron density independent of the ionization potential for a particular transition.…”
Section: Stark Width Regularitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Influence of electron density and temperature on Stark broadening of spectral lines, within spectral series of potassium isoelectronic sequence, have been studied before Equation (1) has been applied in regularity analyzing procedure. Regularity approach used in present paper has been successfully applied previous articles of our group [8][9][10][11][12][13][14][15], where other emitters were analyzed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also the dependence of electron-and proton-impact Stark widths on the upper-level ionization potential within different series of spectral lines of neutral magnesium (Tapalaga et al 2011) and as a function of charge on the atomic core have been evaluated and discussed. This kind of trend and regularity analysis can be useful for the prediction of Stark broadening parameters and therefore for the spectroscopic diagnostic of astrophysical plasmas.…”
Section: Collision Processesmentioning
confidence: 99%